Perbedaan Kesegaran Jasmani antara Siswa yang Berekonomi Tinggi dengan Siswa Berekonomi Rendah di SMA Negeri 5 Lubuklinggau - Muhammad Supriyadi; Muhammad Suhdy (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2020)
he purpose of this study was to obtain information about the differences in physical fitness between students with high economics and students with low economics at SMA Negeri 5 Lubuklinggau. This type of research is Ex Pos Facto Research, that a study was conducted to examine events that had occurred and then look at backward to know the factors that can cause this incident. The population of this study were high-economic students and low-economic students, amounting to 50 students. The sample collection technique is total sampling. Which is total sampling is said to be saturated (complete) if the entire population is sampled. The tool used to collect data is the Indonesian physical fitness test, then analyzed with the statistical t test technique. The results obtained from this study are as follows the difference in physical fitness between high-economic students and low-economic students that is equal to 1.87 and ttable 1.68. So the conclusion there are differences in the level of physical fitness between students with low economics and students with high economics at SMA Negeri 5 Lubuklinggau Keywords: Differences in Physical Freshness